Cranberry Proanthocyanidins Mitigate Reflux-Induced Transporter Dysregulation in an Esophageal Adenocarcinoma Model - Yun Zhang; Katherine M. Weh; Bridget A. Tripp; Jennifer L. Clarke; Connor L. Howard; Shruthi Sunilkumar; Amy B. Howell; Laura A. Kresty (Pharmaceuticals, 2023)
We recently reported that cranberry proanthocyanidins (C-PACs) inhibit esophageal adenocarcinoma (EAC) by 83% through reversing reflux-induced bacterial, inflammatory and immune-implicated proteins and genes as well as reducing esophageal bile acids, which drive EAC progression. This study investigated whether C-PACs’ mitigation of bile reflux-induced transporter dysregulation mechanistically contributes to EAC prevention. RNA was isolated from water-, C-PAC- and reflux-exposed rat esophagi with and without C-PAC treatment. Differential gene expression was determined by means of RNA sequencing and RT-PCR, followed by protein assessments. The literature, coupled with the publicly available Gene Expression Omnibus dataset GSE26886, was used to assess transporter expression levels in normal and EAC patient biopsies for translational relevance. Significant changes in ATP-binding cassette (ABC) transporters implicated in therapeutic resistance in humans (i.e., Abcb1, Abcb4, Abcc1, Abcc3, Abcc4, Abcc6 and Abcc10) and the transport of drugs, xenobiotics, lipids, and bile were altered in the reflux model with C-PACs’ mitigating changes. Additionally, C-PACs restored reflux-induced changes in solute carrier (SLC), aquaporin, proton and cation transporters (i.e., Slc2a1, Slc7a11, Slc9a1, Slco2a1 and Atp6v0c). This research supports the suggestion that transporters merit investigation not only for their roles in metabolism and therapeutic resistance, but as targets for cancer prevention and targeting preventive agents in combination with chemotherapeutics.